BISNIS E-COMMERCE: KEKHAWATIRAN, KEANDALAN TRANSAKSI, PERLINDUNGAN DAN KEAMANAN ATAS INFORMASI - Widarno, Bambang (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
Abstract Growth of information technology require strong infrastructure. Start from readiness of human resource, network, software, and hardware. Appearance of Internet push formed its new market, integrated market with electronic network. care of Consumer to risk of arising out from business of e-commerce is hit expression of business practice, transaction reliability, and also protection of security for information. Criterion of security of transaction entered by into website supported by existence webtrust programme. There is seven standard of guarantee of security of webtrust that is: privacy, business practices and transaction, integrity, security, non-repudiation, security, confidentiality, availability, and customized disclosure. Election of standard of guarantee of security correspond to type of effort what being based on B2C, B2B, B2G Or B2E. To get seal of Webtrust have to fulfill principle and criterion specified by organization of profession got license from organization of international profession in giving service webtrust. By de facto webtrust represent standard which can be used internationally. For company got seal of webtrust for website will obtain get belief from society compared to by situs e-commerce of other; dissimilar which do not own the seal. Keywords: e-commerce, webtrust, segel webtrust, Webtrust’s seven assurance standards